Effects of an Adaptogenic Extract on Electrical Activity of the Brain in Elderly Subjects with Mild Cognitive Impairment: A Randomized, Double-Blind, Placebo-Controlled, Two-Armed Cross-Over Study - Wilfried Dimpfel; Leonie Schombert; Ingrid K. Keplinger-Dimpfel; Alexander Panossian (MDPI AG, 2020)
Background: The current and potential uses of adaptogens are mainly related to treatment of stress-induced fatigue, impaired cognitive function, mental illness, and behavioral- and age-related disorders. However, clinical evidence regarding the efficacy of adaptogens is limited. The primary aim of this study is to determine whether a combination of adaptogenic plant extracts from Andrographis paniculata and Withania somnifera (Adaptra® Forte) could be used as effective and safe treatment for impaired cognitive, memory, or learning ability functions and sleep disorders. Methods: The changes in electroencephalogram (EEG) frequency ranges in 17 different brain regions, psychometric tests of cognitive performance, as well as standard questionnaires of assessment of mood and sleep were measured after single and repeated administration of Adaptra® or placebo for four weeks and after a two-week treatment-free follow-up period within a randomized, double-blind, placebo-controlled two-armed cross-over study. Results: Adaptra® Forte significantly improved cognitive performance in the d2-Test for attention and the concentration performance test after four weeks’ treatment, and was positively correlated with increases in δ and θ power in the quantitative EEG compared with placebo during cognitive challenges. Conclusion: The results of this study suggest that Adaptra® Forte exhibits a calming and anxiolytic effect without sedation, and is associated with overall stress-protective activity.